Formation of a Diffraction Field During Dynamic Scattering of Slow Neutrons in a Deformed Crystal - Shahverdyan, A. V.
The problem of diffraction of slow neutrons with a de Broglie wavelength λ ~10-10 m in a crystal with a deformed lattice is considered. Based on the Hamilton equations describing the dynamic diffraction of slow neutrons, the features of the formation of a dynamic diffraction field in a lattice in various regions of the deformation field characteristics, including weak fields, slowly changing fields and rapidly changing fields are discussed. Using a particular example of a deformation field with a displacement field quadratic in coordinates, analytical solutions are obtained for the wave functions of transmitted and reflected lattice waves.
Keywords: Physics